Anion Recognition by Aliphatic Helical Oligoureas. Issue 44 (4th October 2016) - Diemer, Vincent; Fischer, Lucile; Kauffmann, Brice; Guichard, Gilles
Abstract: Invited for the cover of this issue is the group of Gilles Guichard at the University of Bordeaux. The image depicts the interaction between a 2.5‐helical oligourea foldamer and an anionic guest symbolized as a soccer ball. Read the full text of the article at10.1002/chem.201602481 . Abstract : " The ability to tune molecular recognition properties of foldamers by precise projection of arrays of side chains in a sequence‐dependent manner opens multiple challenging directions with far‐reaching development and application potential ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 15684 ff. (DOI:10.1002/chem.201602481 ).